Indicators of the right to a housing appropriate, in the interpretation authorized in the Covenant DESC: Evaluation of the housing programme (ARQUISUR Revista, 2014)
The problem dealing with the article concerns al ¿what is the joint between the legal, political, economic and social aspects in order to the right to adequate housing? ¿What variables and indicators are respected in their realization? ¿What indicators are abused and in what was improved, with regard to the previous housing situation? The empirical work refers to the process of relocation of the inhabitants of a precarious settlement, and its impact on social relationships and new conditions of habitability, analyzing the arguments that the various actors come into play, ensuring the purpose of increasing the recovery of land, and deepen the socio-spatial segregation. Methodologically, we work with different sources, both primary (interviews semi structured staff and families, then processed with software Atlas Ti) as secondary. The results visibilizan a policy inefficient, ineffective and unsustainable, with effects diametrically opposed to the growing international recommendations and, even, to the specified requirements in the rules of the different territorial levels, where the prevailing private gains, above appropriation the right to the enjoyment of the collective construction of the city.